Unfolded Protein Response as a Compensatory Mechanism and Potential Therapeutic Target in PLN R14del Cardiomyopathy. Issue 5 (3rd August 2021) - Feyen, Dries A.M.; Perea-Gil, Isaac; Maas, Renee G.C.; Harakalova, Magdalena; Gavidia, Alexandra A.; Arthur Ataam, Jennifer; Wu, Ting-Hsuan; Vink, Aryan; Pei, Jiayi; Vadgama, Nirmal; Suurmeijer, Albert J.; te Rijdt, Wouter P.; et al.
Abstract : Background: Phospholamban (PLN) is a critical regulator of calcium cycling and contractility in the heart. The loss of arginine at position 14 in PLN (R14del) is associated with dilated cardiomyopathy with a high prevalence of ventricular arrhythmias. How the R14 deletion causes dilated cardiomyopathy is poorly understood, and there are no disease-specific therapies. Methods: We used single-cell RNA sequencing to uncover PLN R14del disease mechanisms in human induced pluripotent stem cells (hiPSC-CMs). We used both 2-dimensional and 3-dimensional functional contractility assays to evaluate the impact of modulating disease-relevant pathways in PLN R14del hiPSC-CMs. Results: Modeling of the PLN R14del cardiomyopathy with isogenic pairs of hiPSC-CMs recapitulated the contractile deficit associated with the disease in vitro. Single-cell RNA sequencing revealed the induction of the unfolded protein response (UPR) pathway in PLN R14del compared with isogenic control hiPSC-CMs. The activation of UPR was also evident in the hearts from PLN R14del patients. Silencing of each of the 3 main UPR signaling branches (IRE1, ATF6, or PERK) by siRNA exacerbated the contractile dysfunction of PLN R14del hiPSC-CMs. We explored the therapeutic potential of activating the UPR with a small molecule activator, BiP (binding immunoglobulin protein) inducer X. PLN R14del hiPSC-CMs treated with BiP protein inducer X showed a dose-dependent amelioration of the contractility deficit in both 2-dimensional cultures and 3-dimensional engineered heart tissues without affecting calcium homeostasis. Conclusions: Together, these findings suggest that the UPR exerts a protective effect in the setting of PLN R14del cardiomyopathy and that modulation of the UPR might be exploited therapeutically. Abstract : Supplemental Digital Content is available in the text.